Monitoring of Physiological and Parasites Status of Bawean Deer (Axis Kuhlii) in Its Habitat as a Baseline for Wildlife Conservation Endeavor - Wisnu Nurcahyo; Devita Anggraeni; M. A. Imron (Jurnal Sain Veteriner, 2015)
The research on physiological and reproduction status of Bawean deer (Axis kuhlii) in its habitat has been conducted, to understand and to find out as a basic information on Bawean deer (Axis kuhlii) in its habitats abaseline data for wildlife conservation efforts. The deer is categorized as an endangered animal, therefore, more attention was given toward Bawean deer conservation. Habitat changes, loss of habitat, fragmentation and illegalhunting might caused the wild animals become more marginalized and the populations have been declined. Therefore, it is needed to have research as an effort to save Bawean deer in its natural habitat. This research activity covered monitoring on physiological and reproduction status, and also the examination of deer's feces samples was parasite coprological data that serve as a basic consideration data in conservation and determination of Bawean deers health in the nature and/or conservation. The research was done in Bawean Island, Gresik and East Java, by taking faces of Bawean deers in the nature and conservation. Data gathering of physiological and reproduction status were done by examining deer's condition, either directly in conservation or in its habitat, and also by interviewing people around the forest. The data on physiological status, behavior monitoring, reproduction status, faces samples, blood, food analysis, and interview result were analyzed descriptively. Some worm eggs were found during feces examination, those were Strongyl, Strongyloides sp, Trichuris sp, Fasciola gigantica and Oocysta coccidia. The result showed that the same parasites were found in the cattle and goat raised by people around in the vicinity of the forest, meaning, there was an interaction between wildlife andlivestock. According to the result, it is needed to monitor the physiological status of Bawean deers routinely since Bawean deers is classified as endangered species.